Summary of 1980-1982 climatic data collected in the Southern Rangelands Development Unit - Haile-Selassie, A.; Bille, Jean-Claude (International Livestock Centre for Africa, 1983)
Summarizes rainfall & temperature data collected in the weather stations established & operated by RDP & ILCA in south-western Sidamo, Ethiopia, from 1980 to 1982.